The amazing vanishing transistor act. - Geppert, L. (IEEE spectrum)
Radical changes are in the offing for transistors as their dimensions shrink to a few tens of nanometers. In 10 years time, the gate length-the market for gauging how small the transistor is-will be roughly one-fifth the size of the smallest in production today, only 10 nm instead of today's 50 nm. To get to that size and ensure that the transistor still operates will require many changes: to improve performance, silicon will be mixed with a semiconductor like germanium to produce a more spacious, strained crystalline structure that lets electric charge carriers move faster; to reduce the leakage of current that drives up power consumption, gate oxides will be made of materials with more than eight times the dielectric constant (k) of today's silicon dioxide; for better control of the transistor's on and off states, gates will be of metal, instead of polysilicon; and for better control and (again) to reduce power consumption, gates themselves will be doubled up so that two will do the job a single gate does now. Among these techniques, strained silicon is the only one to have been commercialized so far. The rest are still at various stages of R&D.